Determination of polycyclic aromatic hydrocarbons in urban runoff samples from the ‘‘Le Marais’’ experimental catchment in Paris centre - Gonzalez, A.; Moilleron, R.; Chebbo, G.; Thevenot, D.R. (Polycyclic Aromatic Compounds, 2000)
A study for assessing the sources and fate of pollutants during their transport within urban catchment was carried out in the central Paris district, ‘‘Le Marais’’. 16 polycyclic aromatic hydrocarbons were assessed, according to the EPA list, in different types of runoff from a town centre and wet weather waste waters at the outlet of the catchment. PAHs were found predominantly in particulate phase whatever the sample. The median levels found in the different runoffs ranged from below the detection limit (i.e. 1 ng.L-1) to 215 ng.L-1. For the combined sewer outlet, it was 204 ng.L-1. Phenanthrene, anthracene, fluoranthene and pyrene were the most observed compounds. The PAH runoff contents were compared to the combined sewer outlet during wet weather and the total atmospheric fallout. The results show the major role of the atmosphere as a pollution vector as well as the high contribution of the sewer network.